2012
DOI: 10.1155/2012/635451
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Suppressor Macrophages Induced by Mycobacterial and Protozoal Infections in relation to Alternatively Activated M2 Macrophages

Abstract: In the advanced stages of mycobacterial infections, host immune systems tend to change from a Th1-type to Th2-type immune response, resulting in the abrogation of Th1 cell- and macrophage-mediated antimicrobial host protective immunity. Notably, this type of immune conversion is occasionally associated with the generation of certain types of suppressor macrophage populations. During the course of Mycobacterium tuberculosis (MTB) and Mycobacterium avium-intracellulare complex (MAC) infections, the generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 101 publications
1
57
0
Order By: Relevance
“…5). This mode of gene expression is clearly distinguishable from those of typical M1 MΦs and M2 MΦs23527. Notably, MIS-MΦs show high-level expression of CCR7 and some M2 MΦ-specific IL-10, Ym1, and CD163 genes (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…5). This mode of gene expression is clearly distinguishable from those of typical M1 MΦs and M2 MΦs23527. Notably, MIS-MΦs show high-level expression of CCR7 and some M2 MΦ-specific IL-10, Ym1, and CD163 genes (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…The results suggested that IL‐17A −/− mice with ROP expressed relatively low levels of inflammatory cytokines with statistical significance compared with WT controls (MCP‐1, intercellular adhesion molecule 1, VEGF, TNF‐ α , inducible nitric oxide synthase, interferon‐ γ , IL‐1 β , IL‐6, Toll‐like receptor 4 and IL‐12), indicating potential roles of IL‐17A in M1 polarization. Also, according to the functional profiles of M1 and M2 macrophages introduced by Haruaki Tomioka et al . and the findings we detected, significant high levels of Fizz1, transforming growth factor‐ β , IL‐1RA and CD206, and low levels of TNF‐ α , MHC II and IL‐6 at P17 suggested a predominant mixed M2a and M2c phenotype in IL‐17A deficiency (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it is preferable that signatures of macrophage subtypes may not exclude one another but display an overlapping effect. Based on the data presented and the functional profiles of M1 and M2 macrophages introduced by Haruaki Tomioka et al ., the study believed that IL‐17A neutralization alleviated inflammation and facilitated tissue repair in ocular NV by modulating macrophage polarization toward the M2 phenotype and reduced expression of VEGF from M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…They also efficiently produce other cytokines, including IL-1b, TNF-a, and IL-6, and participate as inducers as well as effector cells in polarized Th1 responses, and mediate resistance against intracellular parasites and tumors. 25 As such, for comparison and appropriate clarification of the roles of M2 macrophages in cellular transitions and other cell activities, native and M1macrophages should be included to rule out the influence of these macrophage types in such processes.…”
Section: M2-polarized Tams Promoted Emt Of Pancreatic Cancer Cells C-mentioning
confidence: 99%